Melatonin Improved Anthocyanin Accumulation by Regulating Gene Expressions and Resulted in High Reactive Oxygen Species Scavenging Capacity in Cabbage - Zhang, Na; Sun, Qianqian; Li, Hongfei; Li, Xingsheng; Cao, Yunyun; Zhang, Haijun; Li, Shuangtao; Zhang, Lei; Qi, Yan; Ren, Shuxin; Zhao, Bing; Guo, Yang-Dong (Frontiers in Plant Science, 2016)
In this work, we found that exogenous melatonin pretreatment improved anthocyanin accumulation (1- to 2-fold) in cabbage. To verify the relationship with melatonin and anthocyanin, an Arabidopsis mutant, snat, which expresses a defective form of the melatonin biosynthesis enzyme SNAT (Serotonin N-acetyl transferase), was employed. Under cold conditions, the foliage of wild-type Arabidopsis exhibited a deeper red color than the snat mutant. This finding further proved that exogenous melatonin treatment was able to affect anthocyanin accumulation. To gain a better understanding of how exogenous melatonin upregulates anthocyanin, we measured gene expression in cabbage samples treated with melatonin and untreated controls. We found that the transcript levels of anthocyanin biosynthetic genes were upregulated by melatonin treatment. Moreover, melatonin treatment increased the expression levels of the transcription factors MYB, bHLH, and WD40, which constitute the transcriptional activation complex responsible for coordinative regulation of anthocyanin biosynthetic genes. We found that free radical generation was downregulated, whereas the osmotic adjustment and antioxidant capacities were upregulated in exogenous melatonin-treated cabbage plants. We concluded that melatonin increases anthocyanin production and benefits cabbage growth.